Industrial Era Islamic Education Revolution 4.0: Strategy for Optimizing ICT Integration in Curriculum Education Study Programs - Hamdan; Rusdiana; Tarwilah; Suraijiah; Rusdiah; M. Ramli (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2024)
This study investigates the strategic optimization of Information and Communication Technology (ICT) integration within the curriculum education programs at the Tarbiyah Faculty of UIN Antasari Banjarmasin, in the context of the Industrial Era Islamic Education Revolution 4.0. Using a mixed-methods approach, the research explores the effectiveness and challenges of ICT integration in enhancing pedagogical practices, student learning outcomes, and institutional strategies. The study combines qualitative narratives and quantitative data to assess the impact of ICT, focusing on teacher training, resource accessibility, and alignment with industrial era demands. The results show a moderate level of ICT adoption among students and faculty, with noticeable variations across disciplines. Key findings highlight the necessity for tailored ICT integration strategies to accommodate specific subject requirements and pedagogical preferences. Teacher training and continuous technical support emerge as critical factors for the effective use of ICT in teaching practices. Additionally, ICT’s role in enhancing access to educational resources and fostering student engagement is identified as contributing to improved learning outcomes. Furthermore, aligning ICT integration with the demands of the industrial era is crucial, ensuring that students acquire the digital skills needed for success in the digital economy. These findings provide essential insights for developing strategic frameworks to optimize ICT integration, supporting innovation and excellence in Islamic education.